EP630 Assumption of responsability of the uterine sarcoma, experiment of the service of medical oncology center pierre and marie curie. (CPMC) algiers, algeria. (1st November 2019) - Hadjarab, F; Chekman, CE; Taibi, A; Bouzid, K
Abstract : Introduction/Background: The uterine sarcomas account for 1 to 5% of the malignant tumors of the uterus. Distribution: - T. epithelial mixed andmesenchymaleusesl (T mülleriennes mixed) (50-60%): represented by the carcinosarcome, adenosarcome, - léiomyosarcome. (35%) -sarcoma of the stroma (chorion cytogenous lowrank Bad forecast except SBS 10%) of low rank, and undifferentiated. Treatment: the improvement of the surgery of theprimary tumour and metastases is essential. RTEplaces auxiliary chemotherapy remains thesensitivity and local control, this, depend, according to the histological type, Place given oftherapeutic targeted, and, to define: the trabectidine drug. Methodology: The retrospective study of 19 case of uterine sarcoma support to the service of the medical oncology with the CPMC course of the period has 2004 2011. Results: Median age of the diagnosis: 51 years. The diagnosis made on the histological examination revealed in the operating room. It histological 3varieties: 10 cases of léiomyosarcome, 3 cases ofcarcinosarcome distinguish, 4 cases of sarcomaof stroma (chorion cytogenous of the endometer) stage IV of tumor was found in 50% of the tumors, then of 25% III. For the stage is closely related to the phase of tumor; The forecast treatment is primarily an exclusive radical surgery in 5 cases, 12 cases have benificiee of atreatment of chemotherapy in the event ofrepetition or metastatic. Ifosfamide/doxorubicine, DOCÉTAXEL/gemcitabine PXL/CARBO. The protocols used radiochimio-concomitant was carried out at a patient presenting one To theanswer: RC (7 cases); RP (2 case); Ms (4case); failed (4case) carcinosarcome to become: 9 patients alive in remission, 4patients died, Sick alive: 4. Conclusion: The sarcoma of the uterus is the badtumour prognostic one, the surgery of the primary tumor and metastases is essential, chemotherapy is booked in the case of arepetition or metastatic. We pay in this study, the Algerian experiment in favor of uterine sarcomas. Disclosure: No conflict of interest.